2015
DOI: 10.1038/onc.2015.244
|View full text |Cite
|
Sign up to set email alerts
|

TRM6/61 connects PKCα with translational control through tRNAiMet stabilization: impact on tumorigenesis

Abstract: Accumulating evidence suggests that changes of the protein synthesis machinery alter translation of specific mRNAs and participate in malignant transformation. Here we show that protein kinase C α (PKCα) interacts with TRM61, the catalytic subunit of the TRM6/61 tRNA methyltransferase. The TRM6/61 complex is known to methylate the adenosine 58 of the initiator methionine tRNA (tRNAi(Met)), a nuclear post-transcriptional modification associated with the stabilization of this crucial component of the translation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 47 publications
(50 reference statements)
4
59
0
Order By: Relevance
“…The cellular level of tRNA iMet is known to significantly impact translation initiation and cell proliferation (Macari et al, 2016; Pavon-Eternod et al, 2013). Indeed, a noticeably increased cell proliferation was observed in the ALKBH1 knockdown cells compared to control cells (Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…The cellular level of tRNA iMet is known to significantly impact translation initiation and cell proliferation (Macari et al, 2016; Pavon-Eternod et al, 2013). Indeed, a noticeably increased cell proliferation was observed in the ALKBH1 knockdown cells compared to control cells (Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…TRMT6 and TRMT61A form a methyltransferase complex and catalyze the methylation of the N1 position on adenosine residues in mRNA. Prior studies have shown that deletion of the TRMT6/61 complex can reduce glioma cell proliferation and increase cell death 33 . Additional studies showed that TRMT6 frameshift mutations could potentially contribute to colorectal cancer 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some RMPs of m 1 A, both writers and erasers, seem to involve in the progression of GBM (Figure 2, m 1 A part). TRMT6 and TRMT61A expression is significantly upregulated in highly aggressive GBM compared with grade II/III gliomas [79]. TRMT61A is a target of HIF1A and is dowregulated after c-Myc inhibition in GBM under hypoxia [138].…”
Section: Rna M 1 a Modification In Gbmmentioning
confidence: 99%